Human Olfactory Mesenchymal Stem Cells Are a Novel Candidate for Neurological Autoimmune Disease - Xiao, Chongjun; Lu, Di; Chen, Jinshuo; Chen, Xiaoyan; Lin, Huizhu; Huang, Mudan; Cheng, Shimei; Wang, Yuge; Liu, Qiuli; Zheng, Haiqing (Frontiers in Pharmacology, 2021)
Abstract Background Human Olfactory Mesenchymal Stem Cells (OMSC) have become a novel therapeutic option for immune disorder or demyelinating disease due to their immunomodulatory and regenerative potentials. However, the immunomodulatory effects of OMSC still need to be elucidated, and comparisons of the effects of different MSC are also required in order to select an optimal cell source for further applications. Results In animal experiments, we found neural functional recovery and delayed EAE attack in OMSC treatment group. Compared with umbilical cord-derived mesenchymal stem cells (UMSC) and control group, OMSC treatment group had a better neurological improvement, lower serum levels of IFN-γ, and a lower proportion of CD4+IFN-γ+ T splenic lymphocyte. We also observed OMSC effectively suppressed CD4+IFN-γ+ T cells proportion in vitro when co-cultured with human peripheral blood-derived lymphocytes. OMSC-mediated immunosuppressive effect on human CD4+IFN-γ+ T cells was attenuated by blocking cyclooxygenase activity. Conclusions Our results suggest that OMSC treatment delayed the onset and promoted the neural functional recovery in EAE mouse model possibly by suppressing CD4+IFN-γ+ T cells. OMSC transplantation might become an alternative therapeutic option for neurological autoimmune disease.